Comparison of oral hygiene status among 6-14 year old students of public and private schools of Rajbiraj, Saptari, Nepal - Bhagat, TK; Shrestha, A; Yadav, TN (Journal of College of Medical Sciences-Nepal, 2015)
Aim To determine the oral hygiene status of 6-14 years old school children in Rajbiraj, Nepal. Materials and Methods Three hundred school children from public and private schools were examined for oral hygiene status using OHI(S). Descriptive statistics and independent sample t-tests were done. Results There was no significant difference in the oral hygiene status among gender, but the oral hygiene status of the children in private schools was better than that of the public school. Conclusion Large number of public school children had poor oral hygiene compared to private school children. Hence, oral health education programs should be conducted on a frequent basis to improve their oral hygiene status. DOI: http://dx.doi.org/10.3126/jcmsn.v10i1.12763 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(1); 17-21